Biophysical and Biocultural Upheavals in Mesoamerica, a Conservation Perspective: Mountains, Maize-Milpa, and Globalization - del Castillo, Rafael F.; Rivera-García, Raúl (Frontiers in Forests and Global Change, 2022)
Three upheavals shaped southern Mexico to Panama (SMP) biodiversity: 1. The Great American Interchange that allowed migrations between the Neotropical and the Nearctic biogeographic realms; 2. human colonization with the generation of Mesoamerican cultures; and 3. the Spaniards’ arrival and globalization. Tectonic events generated a narrow piece of land with steep topography and high environmental heterogeneity, demanding high levels of local adaptation. Habitat size is usually restricted and reduced by frequent disturbances. Topography imposes few options for individuals forced to displace. Thus, extinction risks should be unusually high. Humans initiated an ongoing defaunation process and introduced the maize and the milpa, an itinerant maize-based slash-and-burn polyculture, which depends on revegetation to re-establish soil fertility. Also, the Milpa is a most important pre-Hispanic legacy, a biocultural and landrace reservoir actively affecting landscape configuration, succession, soil development, and the genetic architecture of the species. Unprecedented human epidemics and soil, biodiversity, and culture erosion followed behind the Spanish aftermath and the subsequent globalization. >63 million people and ≈100 ethnic groups inhabit SMP (2020), which, with the biota, share the same problems of climate change, disturbance, and acculturation. SMP has been the scenario of severe climate change, fastest and deadliest extinction events (amphibians), a most spectacular exotic-species invasion (Africanized honeybees), and accelerated deforestation, defaunation, and acculturation. Biocultural conflicts between native and non-native people are globalization byproducts and sources of habitat destruction and species decline. Bottom-up initiatives are likely the best option for conservation in indigenous areas, whereas honest (i.e., with truly conservation intentions) top-down initiatives are helpful if the affected people are considered subjects (no objects) of conservation plans. We suggest some unique areas requiring conservation attention and analyzed current conservation initiatives. Not a single initiative is best suited for all conservation needs in SMP. Protection of all successional stages is critical for resilience and revegetation. Conservation of the milpa system (crop fields and subsequent fallows) is an optimal option for minimizing tradeoffs between conservation and people needs and safeguarding traditional culture and local landraces but is limited to areas with indigenous people and may not work for species with large home ranges.